Instructional and Professional Experiences of Multigrade Teachers - Valeria-Mayola, Ma. Jonina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the instructional and professional experiences of multigrade teachers in the Division of Malaybalay City during the 2025–2026 school year. Anchored on Differentiated Instruction Theory by Tomlinson and Bandura’s Self-Efficacy Theory, the study examined how multigrade teachers adapt instructional practices and develop professionally while handling multiple grade levels in one classroom. Using a qualitative transcendental phenomenological design by Moustakas (1994), the study involved six purposively selected multigrade teachers from public elementary schools. Data were gathered through validated semi-structured interviews conducted in three sessions per participant and analyzed using thematic analysis. Findings revealed that multigrade teachers constantly adjusted instruction to address learners’ varied needs, abilities, and learning paces through differentiated activities, flexible grouping, and adaptive teaching strategies. Teachers also experienced resource scarcity, overcrowded classrooms, and limited instructional materials, yet sustained instruction through creativity, improvisation, and resilience. Another major challenge involved managing multiple grade levels within limited instructional time, requiring structured routines, prioritization of essential competencies, and effective time management. In terms of professional advancement, teachers developed greater confidence, competence, resilience, and self-efficacy through repeated teaching experiences, collaboration with colleagues, Learning Action Cell (LAC) sessions, trainings, and professional development activities. The study concluded that multigrade teaching is a continuous process of adaptation, collaboration, and professional growth that demands flexibility, commitment, and learner-centered instruction. The study recommended strengthening professional development, instructional supervision, resource provision, and institutional support for multigrade teachers and schools. The findings support Sustainable Development Goal 4 (Quality Education) by promoting inclusive and equitable learning opportunities, particularly for learners in remote and underserved communities. The study also contributes to sustainable educational development by supporting teacher resilience, instructional effectiveness, and equitable access to quality education in marginalized areas.
Keywords: Classroom Management; Differentiated Instruction; Multigrade Classes; Professional Advancement; Resource Scarcity; Self-Efficacy; Time Management; Transcendental Phenomenology